2021
DOI: 10.1002/2688-8319.12099
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning object detection to estimate the nectar sugar mass of flowering vegetation

Abstract: Floral resources are a key driver of pollinator abundance and diversity, yet their quantification in the field and laboratory is laborious and requires specialist skills. Using a dataset of 25,000 labelled tags of fieldwork‐realistic quality, a convolutional neural network (Faster R‐CNN) was trained to detect the nectar‐producing floral units of 25 taxa in surveyors’ quadrat images of native, weed‐rich grassland in the United Kingdom. Floral unit detection on a test set of 50 model‐unseen images of comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…This high score makes the knowledge encapsulated by model actionable, i.e., it can be applied in practice for automatic large-scale wildflower monitoring. Other F-RCNN object detection models for wildflower monitoring are published by Hicks et al [39] and Gallman et al [60]. However, these studies, having 25K and 10K annotations respectively, collected wildflower data in limited period of one flowering season (May till August) and their models are able to identify and count only 25 flowering plant species, half the number of species that our model can handle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This high score makes the knowledge encapsulated by model actionable, i.e., it can be applied in practice for automatic large-scale wildflower monitoring. Other F-RCNN object detection models for wildflower monitoring are published by Hicks et al [39] and Gallman et al [60]. However, these studies, having 25K and 10K annotations respectively, collected wildflower data in limited period of one flowering season (May till August) and their models are able to identify and count only 25 flowering plant species, half the number of species that our model can handle.…”
Section: Discussionmentioning
confidence: 99%
“…Both support the monitoring use case, i.e., the use of object detection models that can classify and localize . The Nectar dataset [39] consists of nearly 2000 Canon Powershot G10 (14.7 Mpixels) images of flowering plant species collected in one flowering season in one habitat type, viz. weed-rich grasslands in the UK.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Object detection models are trained with images containing tagged bounding boxes around objects of interest. Hicks et al [20] presented a first object detection model that was able to count 25 different wildflower species in images. In FlowerPower, the concept of Hicks et al [20] is expanded to a more advanced data-centric object detection model that can be used to count 100+ different wildflower species and a comprehensive software platform that supports various enduser scenarios.…”
Section: Ai For Biodiversity Monitoringmentioning
confidence: 99%
“…Empirically, Reilly et al (2020) found that "Bluecrop" fields would require 16.7-26.3 bees per 100 m row to maximize fruit weight. Pollinator density estimates should always be associated with a flower count in pollination empirical studies (Chabert et al, 2022), highlighting the importance of developing simple and fast flower monitoring approaches with new methods such as image analysis with deep learning (Farjon et al, 2020;Hicks et al, 2021). Flower monitoring approaches could also be used by growers and crop advisors to assess pollination and inform pollination management.…”
Section: Managed Honey Beesmentioning
confidence: 99%